Effect of Clopidogrel on Corrosion Inhibition of Mild Steel in 1 M H2SO4 - Dubey, R.S.; Singh, K.U. (Asian Journal of Chemistry, 2011)
The inhibitive action of pharmaceutically active clopidogrel on corrosion of mild steel in 1M H2SO4 was investigated by using weight loss, corrosion potential, potentiodynamic polarization and surface analytical techniques. The change in electrochemical parameters observed by variation on inhibitor concentration within the range of 10-500 ppm favours its adsorption. The compound influences the anodic dissolution of mild steel as well as hydrogen evolution reaction in 1M H2SO4. Morphology of the mild steel specimens was examined using scanning electron microscopy in presence and absence of inhibitor. The inhibition was due to adsorption of inhibitor molecule on metal surface. Mechanism of adsorption of clopidogrel on the surface of mild steel is proposed for its inhibition behaviour. The adsorption characteristics of the inhibitor were approximated by Langmuir adsorption isotherm. An adherent layer of inhibitor on mild steel surface acted as barrier between metal and aggressive solution.